The impact of vicarious trauma on Aboriginal and/or Torres Strait Islander health researchers - Anne-Marie Eades; Maree Hackett; Margaret Raven; Hueiming Liu; Alan Cass (Sax Institute, 2021)
Aim: To describe and reflect on an Aboriginal researcher's experience of vicarious trauma arising from a qualitative study of Aboriginal and Torres Strait Islander women with chronic disease. Methods: In-depth semistructured interviews with thematic analysis were undertaken to explore the psychosocial factors experienced by Aboriginal and Torres Strait Islander women as they managed their chronic disease. An 'Indigenous women's standpoint theory' approach was adopted to frame discussion. This approach gives strength and power to the voice of Aboriginal and Torres Strait Islander women and their diverse cultural lived experiences. The raw and often brutal realities this approach exposed had a triggering impact on the Aboriginal team member for whom these realities were familiar. Interviews were conducted with participants from four Aboriginal Medical Services from urban, rural and remote Australia. Analysis of the interviews, and reflection regarding the researcher's experiences, occurred within the context of a multidisciplinary team. Participant selection for the interview study was purposive. Seventy-two participants were selected for this study. The duration of the study was 2 years, and it was undertaken between March and December 2014, and finalised in December 2016. Results: In exploring how Aboriginal and Torres Strait Islander women managed their own health and wellbeing, compelling stories of trauma, domestic violence and generational incarceration were shared with the researcher. Hearing and re-living some of these overwhelming experiences left her feeling isolated and distressed. These compelling stories contributed to her experience of vicarious trauma. Conclusion: When Aboriginal and Torres Strait Islander researchers conduct research in Indigenous communities, we should monitor, prepare for and provide appropriate care and support to researchers to address the potential for vicarious trauma. These considerations are paramount if we are to build the capacity of Indigenous and non-Indigenous researchers to conduct Indigenous health research.